(untitled) (Wahana Didaktika : Jurnal Ilmu Kependidikan, 2024)
Children with special needs are children who require special services that are different from other children in their educational curriculum. Deaf (hearing impaired) is a general term used to describe people who suffer from hearing loss or impairment caused by damaged or non-functioning hearing aids. Good behavior is a human action or activity that leads in a positive direction according to personal experience. The efforts made by teachers are (1) by providing knowledge and understanding using sign language, (2) by providing a sense of empathy for children through sign language instructions, (3) providing examples of good and appropriate behavior through sign language or body language so that they are easy to understand. understood by children with special needs such as the deaf. The reasons for this research are 1). What is your learning method for applying good behavior to Deaf children? 2.) How do you respond if a child has difficulty accepting material related to good behavior? 3). From the results of the implementation of good behavior at school, is there a particular evaluation and what is done by teachers to encourage enthusiasm for learning in children? To find out how teachers try to implement good behavior at SLB Negeri 5 Bengkulu City, researchers took a qualitative approach using data source methods obtained from three types of data sources, namely, data collection techniques in the form of observation, interviews and documentation.